2017
DOI: 10.1108/ijppm-11-2014-0179
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and acquisitions in Brazilian industry: a study of spillover effects

Abstract: Purpose The purpose of this paper is to investigate the effects of different kinds of merger and acquisitions (M&As) on domestic industries’ productivity in the form of technological change (TC) and efficiency change (EC) in the Brazilian extracting and processing industries. Design/methodology/approach Panel data analysis is employed to test the impact of different kinds of M&As spillovers on each component of productivity growth. The database contains data collected from 2007 to 2011 referring to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 93 publications
(155 reference statements)
1
11
0
3
Order By: Relevance
“…Além da capacidade de aprendizagem e absorção, o impacto do IED também depende de outros aspectos relativos ao setor e país de recebimento (ANWAR;NNGUYEN, 2014;BRUHN et al, 2017;DESBORDES;WEI, 2017). A negação dessa hipótese pode dizer respeito ao fato das organizações obterem melhorias a partir do capital estrangeiro, apenas sob a condição de absorção das externalidades oriundas desses investimentos nos seus processos organizacionais (BRUHN et al;NARULA, 2014;DUNNING, 2010).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Além da capacidade de aprendizagem e absorção, o impacto do IED também depende de outros aspectos relativos ao setor e país de recebimento (ANWAR;NNGUYEN, 2014;BRUHN et al, 2017;DESBORDES;WEI, 2017). A negação dessa hipótese pode dizer respeito ao fato das organizações obterem melhorias a partir do capital estrangeiro, apenas sob a condição de absorção das externalidades oriundas desses investimentos nos seus processos organizacionais (BRUHN et al;NARULA, 2014;DUNNING, 2010).…”
Section: Discussionunclassified
“…Ele mostrou que, embora exista a possibilidade do crescimento econômico, o que no setor sucroenergético poderia aumentar a capacidade de moagem das usinas, os seus resultados revelaram um aumento na degradação ambiental, ou seja, não há evidência de que o IED está relacionado com a busca pela sustentabilidade, e consequentemente com a adoção de certificações da área. Além disso, estudos revelaram que o impacto do IED depende da capacidade de absorção que pode variar desde o país de recebimento do investimento, quanto do setor investido, além da capacidade de aprendizagem que as organizações possuem para que haja o benefício do capital estrangeiro (ANWAR; NGUYEN, 2014;BRUHN et al, 2017;DESBORDES;WEI, 2017).…”
Section: As Certificações E O Ied No Setor Sucroenergéticounclassified
See 1 more Smart Citation
“…Bruhn et al () found a positive correlation between technological change and M&A among Brazilian companies. In fact, Gorg and Greenaway () and Buckley et al (, ) argue that reductions in the technology gap ratio are often due to the presence of firms with different technological skills and expertise.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The results show that the type and origin of the bank will affect the final merger efficiency. Bruhn, Calegário, de Carvalho, Campos, and dos Santos (2017) used the Malmquist Productivity Index and regression model to analyze the merger efficiency of Brazil's refined industrial companies from 2007 to 2011. The results show that there is a positive relationship between the effect of technology cooperation and merger.…”
Section: Introductionmentioning
confidence: 99%